The Interconnectivity of ESG Research Within the Realm of Sustainability: A Bibliometric Analysis - Iuliana-Madalina Petrica (Papuc); Chirata Caraiani; Camelia Iuliana Lungu; Liana-Elena Anica-Popa (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Motivation- The relationship between ESG factors and sustainability is a widely debated topic in the literature, but to our knowledge, there is a gap concerning the investigation of links between groups formed with ESG and other sustainability concepts, such as corporate social responsibility (CSR), green economy, circular economy, digitalization, technology, industry 4.0, and industry 5.0. Idea- The objective of this study is to identify the interest of researchers, their visibility, as well as the trends among publications, regarding the ESG factors in relation to other concepts within the realm of sustainability, like CSR, green economy, circular economy, digitalization, technology, industry 4.0, and industry 5.0. Data- The selected sample for the research includes 1430 papers screened from the Web of Science database. Tools- The aim of this study is achieved by conducting a bibliometric analysis, using VOSviewer and PowerBI. Findings- The findings of this study include the interconnectivity of selected concepts, the co-occurrence of authors' keywords, the number of publications over time, as well as the paper types, the publishing activity by journal, the most productive authors, the co-authorship, their affiliation, the papers' length, references, and citations trend, the most cited papers, the publishing activity by country and the collaboration patterns between countries. Contribution- This analysis supports the identification of potential gaps in current ESG-related research and points toward new areas of investigation. It also contributes to the advancement of ESG research and to the achievement of sustainable development goals.
Keywords: M41; 650; ESG; sustainability; CSR; industry 5.0; bibliometric analysis